Analisis atribut toko online terhadap repurchase intention dengan mediasi customer satisfaction di Indonesia - Boni Jovianggi; Yasintha Soelasih (Jurnal Manajemen Maranatha, 2020)
Consumer behavior is currently experiencing changes in shopping. Technological developments cause changes in consumers. Companies see changes in consumer shopping patterns. Consumers buy through not only offline, but also online. Patterns of change are not only for products, but services as well as changes in purchases. This development has led to the emergence of online stores, giving rise to online applications. This study aims to determine whether the attributes of online stores affect repurchase intention in online shopping applications. Besides, this study was also conducted to determine the mediating variable's effect on customer satisfaction on the relationship between online store attributes and repurchase intention. The sampling method used in this study is non-probability sampling with a purposive sampling technique. This study's data were obtained by distributing an online questionnaire to 201 respondents who were account holders and had shopped in an online application. The indicators and variables in this study were tested for their’s validity and reliability before being used in data collection. The validity used is confirmatory factor analysis (CFA) and reliability used is composite reliability (CR) and average variance extracted (AVE). This study uses data analysis method of Structural Equation Modeling (SEM) with Lisrel for Windows 8.70 software to test the research hypotheses. This study's results indicate that the attributes of online stores do not directly have a significant effect on repurchase intention. Online store attributes have a significant effect on repurchase intention by mediation of customer satisfaction.